Severe Postpartum Coagulopathy Without Haemorrhage: A Case Report - Lérias-Cambeiro, Muriel (2018)
Postpartum haemorrhage is an important health issue worldwide, and it can be caused by uterine atony, retained placental tissue, trauma or coagulation disorders. Although coagulopathy represents a rare cause, it is a significant contributor to postpartum haemorrhage with poor outcomes. Associated with high morbidity and mortality rates, postpartum haemorrhage demands prevention, prompt diagnosis and effective management. We describe a unique case of severe coagulopathy caused by underestimated blood loss during caesarean section without postpartum bleeding, in which transfusion requirements were thromboelastometry-guided. This case report depicts how an early multidisciplinary approach and patient-centred care in an obstetric emergency contributes to a positive outcome from a challenging situation, enabling the prevention of an imminent, catastrophic haemorrhage.